Statistical analyses of Endogenous Uveitis Patients (2007–2009) in central Tokyo area and Comparison with Previous Studies (1963–2006). (August 2015) - Nakahara, Hisae; Kaburaki, Toshikatsu; Takamoto, Mitsuko; Okinaga, Kimiko; Matsuda, Junko; Konno, Yasuhiro; Kawashima, Hidetoshi; Numaga, Jiro; Fujino, Yujiro; Amano, Shiro
Abstract Purpose: To investigate the frequencies of the diseases in the new patients with uveitis during 2007–2009 and compare them with previously-reported data from the University of Tokyo Hospital. Methods: We retrospectively analyzed the clinical records of patients who visited the outpatient clinic from January 2007 to December 2009, and compared them with those of 1963–2006. Results: During 2007–2009, 468 new patients visited our hospital. Definite diagnoses were made in 63.0%. Frequent diagnoses include sarcoidosis (9.4%), Vogt-Koyanagi-Harada (VKH) disease (7.9%), herpetic iritis (6.0%), Behçet's disease (5.6%), Posner-Schlossman syndrome (4.3%), HLA-B27-associated uveitis (3.0%), and intraocular malignant lymphoma (2.8%). Compared with our former findings, the ratios of sarcoidosis, herpetic iritis, CMV retinitis, Fuch's heterochromic iridocyclitis, acute retinal necrosis and intraocular lymphoma increased, while that of Behçet's disease decreased. Conclusions: Top three uveitis during 2007–2009 were sarcoidosis, VKH disease, herpetic iritis. Reduced frequency of Behçet's disease was one of the most prominent characteristics.